2013
DOI: 10.1371/journal.pone.0074908
|View full text |Cite|
|
Sign up to set email alerts
|

A Network of HSPG Core Proteins and HS Modifying Enzymes Regulates Netrin-Dependent Guidance of D-Type Motor Neurons in Caenorhabditis elegans

Abstract: Heparan sulfate proteoglycans (HSPGs) are proteins with long covalently attached sugar side chains of the heparan sulfate (HS) type. Depending on the cellular context HS chains carry multiple structural modifications such as sulfate residues or epimerized sugars allowing them to bind to a wide range of molecules. HSPGs have been found to play extremely diverse roles in animal development and were shown to interact with certain axon guidance molecules. In this study we describe the role of the Caenorhabditis el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…With the discovery that ZFP-1 negatively regulates pdk-1, a component of the IIS pathway, via direct repression of pdk-1 transcription (Mansisidor et al 2011), we were prompted to investigate the connection between ZFP-1 and IIS during HSN migration. We found that the zfp-1 (ok554) loss-of-function mutant (Cui et al 2006;Avgousti et al 2013;Cecere et al 2013) and the zfp-1(op481) mutant (Gysi et al 2013)-both of which lead to the generation of mRNAs that contain premature stop codons after the PHD fingers-display HSN undermigration defects (Figure 1, A-C). We used a tryptophan hydroxylase GFP reporter (tph-1:: gfp) that marks the HSNs in adult animals for scoring the migration phenotype.…”
Section: Elegans Zfp-1/af10 Regulates the Migration Of The Hsnsmentioning
confidence: 94%
See 3 more Smart Citations
“…With the discovery that ZFP-1 negatively regulates pdk-1, a component of the IIS pathway, via direct repression of pdk-1 transcription (Mansisidor et al 2011), we were prompted to investigate the connection between ZFP-1 and IIS during HSN migration. We found that the zfp-1 (ok554) loss-of-function mutant (Cui et al 2006;Avgousti et al 2013;Cecere et al 2013) and the zfp-1(op481) mutant (Gysi et al 2013)-both of which lead to the generation of mRNAs that contain premature stop codons after the PHD fingers-display HSN undermigration defects (Figure 1, A-C). We used a tryptophan hydroxylase GFP reporter (tph-1:: gfp) that marks the HSNs in adult animals for scoring the migration phenotype.…”
Section: Elegans Zfp-1/af10 Regulates the Migration Of The Hsnsmentioning
confidence: 94%
“…Moreover, the op481 allele was shown to exhibit an identical axon guidance phenotype as the ok554 allele of zfp-1 (Gysi et al 2013). Surprisingly, however, the axon guidance phenotype in the zfp-1(ok554); sdn-1(zh20) double mutant was dependent upon the presence of the integrated transgene used to visualize the axon guidance defects (Gysi et al 2013).…”
Section: Elegans Zfp-1/af10 Regulates the Migration Of The Hsnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we did not detect any DD/VD axonal 287 defects at either 1G or 100G in this strain (data not shown). However, a previous report 288 cautioned that the oxIs12 transgenic strain affected the expression of X-linked genes involved in 289 axon guidance such as unc-6/netrin and lon-2/glypican genes, altering axon guidance phenotypes 290 in different genetic backgrounds (Gysi et al 2013). In addition, previous studies using electron 291 microscopy have shown that the DD motor neurons can develop in slightly different locations in 292 individual animals (White et al 1976), and the number of axons innervating the dorsal nerve 293 cord can also vary in individual animals (Hedgecock et al 1990).…”
mentioning
confidence: 99%